1998
DOI: 10.1073/pnas.95.3.1044
|View full text |Cite
|
Sign up to set email alerts
|

Defective stratum corneum and early neonatal death in mice lacking the gene for transglutaminase 1 (keratinocyte transglutaminase)

Abstract: The stratum corneum of the skin serves as an effective barrier for maintenance of the internal milieu against the external environment. At the cell periphery of the stratum corneum is the cell envelope, a highly insoluble membranous structure composed of precursor proteins crosslinked by -(␥-glutamyl)lysine bonds. Transglutaminase 1 (TGase 1; keratinocyte TGase), a membrane-bound isozyme of the TGase family, has been proposed to catalyze this process of assembly. Deficient cross-linking of the cell envelope in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
196
1
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 271 publications
(211 citation statements)
references
References 51 publications
10
196
1
4
Order By: Relevance
“…At the genetic level, the loss of barrier function can be caused by an array of defects in the complex machinery required for the proper assembly of keratin ®laments in the corneocyte, the assembly of corni®ed envelope components, the formation of corneocyte adherens junctions, or the assembly of intercorneocyte lipids, as observed in numerous inherited skin diseases or in transgenic mice with dominant or recessive mutations in epidermal components (Nemes and Steinert, 1999;Presland and Dale, 2000;Roop, 1995). Null, frameshift, or point mutations in genes encoding structural proteins of the corneocyte (e.g., keratins, loricrin), in components of the enzymatic machinery that process and cross-link these structural proteins (e.g., transglutaminase 1), in desmosomal cadherins linking corneocytes together (e.g., desmoglein), or in the enzymes that manufacture and process corni®ed envelope and intercorneocyte lipids (e.g., fatty aldehyde dehydrogenase, arylsulfatase C/cholesterol sulfatase) have all been reported to disrupt epidermal barrier function (De Laurenzi et al, 1996;Elias et al, 2001;Huber et al, 1995;Koch et al, 2000;Kubilus et al, 1979;Matsuki et al, 1998;Russell et al, 1995;Shapiro et al, 1978). The data presented in this paper strongly suggest that the abrogation of barrier function is related to abnormal extrusion of vesicular bodies in the transitional layer of the cornifying epidermis, which likely aects the formation of the specialized set of crosslinked intercorneocyte lipids that confer epidermal barrier function in conjunction with the corni®ed envelope.…”
Section: /7mentioning
confidence: 99%
“…At the genetic level, the loss of barrier function can be caused by an array of defects in the complex machinery required for the proper assembly of keratin ®laments in the corneocyte, the assembly of corni®ed envelope components, the formation of corneocyte adherens junctions, or the assembly of intercorneocyte lipids, as observed in numerous inherited skin diseases or in transgenic mice with dominant or recessive mutations in epidermal components (Nemes and Steinert, 1999;Presland and Dale, 2000;Roop, 1995). Null, frameshift, or point mutations in genes encoding structural proteins of the corneocyte (e.g., keratins, loricrin), in components of the enzymatic machinery that process and cross-link these structural proteins (e.g., transglutaminase 1), in desmosomal cadherins linking corneocytes together (e.g., desmoglein), or in the enzymes that manufacture and process corni®ed envelope and intercorneocyte lipids (e.g., fatty aldehyde dehydrogenase, arylsulfatase C/cholesterol sulfatase) have all been reported to disrupt epidermal barrier function (De Laurenzi et al, 1996;Elias et al, 2001;Huber et al, 1995;Koch et al, 2000;Kubilus et al, 1979;Matsuki et al, 1998;Russell et al, 1995;Shapiro et al, 1978). The data presented in this paper strongly suggest that the abrogation of barrier function is related to abnormal extrusion of vesicular bodies in the transitional layer of the cornifying epidermis, which likely aects the formation of the specialized set of crosslinked intercorneocyte lipids that confer epidermal barrier function in conjunction with the corni®ed envelope.…”
Section: /7mentioning
confidence: 99%
“…TG1 is selectively expressed in the suprabasal epidermal layers (Michel et al, 1992) and is unique in that it is anchored to the inner surface of the plasma membrane via myristyl and palmityl linkages attached to a cluster of cysteine residues present in the aminoterminus (Chakravarty and Rice, 1989;Chakravarty et al, 1990;Rice et al, 1990;Phillips et al, 1993;Steinert et al, 1996). Elimination of TG1 expression results in an epidermal scaling phenotype (Kuramoto et al, 2002;Matsuki et al, 1998) that resembles the phenotype observed in lamellar ichthyosis, a human TG1 deficiency disease (Huber et al, 1995). This is because TG1 activity is required for assembly of the envelope structure and other enzymes cannot substitute.…”
Section: Tg1 and Tig3 In Keratinocytesmentioning
confidence: 99%
“…Genetic defects of TGase 1 cause the often devastating disease lamellar ichthyosis (37,38). The homozygous TGase 1 knockout mice show defective CE assembly and die from dehydration a few hours after birth (39).…”
mentioning
confidence: 99%